RELOCATION OF HOME APPLIANCES FACTORY BY USING SYSTEMATICAL LAYOUT PLANNING (SLP) COMBINED WITH FLOW ANALYSIS AND ASSEMBLY PROCESS DESIGN - Baskoro, Yosef Adji; Tanaya, Prianggada Indra; Sofianti, Tanika D. (Jurnal Ilmiah Teknik Industri, 2011)
Every manufacturing company must have experiencing building a layout. Fred.E Meyers has stated that only death and taxes are certain, there exist a third certainty-a plant layout will change, thus many methods to generate layout are established and each has its own purposes and benefits. This research focused on the design of manufacturing facilities supported by in-depth analysis of Assembly process design with a high stresses on the Systematical Layout Planning ( SLP) and Flow Analysis method to facilitate an outcome of layout accordingly to the system needs. This is a real case study conducts with an objective of generating a recommendation layout for Home Appliances Company specifically for television plant